Automated Production of High Rep Rate Foam Targets. (April 2016) - Hall, F; Spindloe, C; Haddock, D; Tolley, M; Nazarov, W
Abstract: Manufacturing low density targets in the numbers needed for high rep rate experiments is highly challenging. This report summarises advances from manual production to semiautomated and the improvements that follow both in terms of production time and target uniformity. The production process is described and shown to be improved by the integration of an xyz robot with dispensing capabilities. Results are obtained from manual and semiautomated production runs and compared. The variance in the foam thickness is reduced significantly which should decrease experimental variation due to target parameters and could allow for whole batches to be characterised by the measurement of a few samples. The work applies to both foil backed and free standing foam targets.